Emulsion filled polysaccharide gels: Filler particle effects on material properties, oral processing, and sensory texture. (September 2019) - Koç, Hicran; Drake, MaryAnne; Vinyard, Christopher J.; Essick, Gregory; van de Velde, Fred; Foegeding, E. Allen
Abstract: Addition of filler particles is a common approach to alter food structure and thereby change sensory properties. The goal of this investigation was to determine how filler particles alter oral processing patterns and sensory texture perception of two model food gels with distinct mechanical properties. Agar gels (brittle) and κ-carrageenan-locust bean gum gels (ductile) were formulated to have similar strength (fracture stress) but different deformability (fracture strain). Increasing the phase volume of oil droplets decreased fracture stress and stress intensity factor of both filled gels, while the main effect on fracture strain and fracture surface energy was observed for the highly deformable κ-carrageenan-locust bean. Adding oil had general effects of decreasing sensory hardness and particle size and increasing the rate of breakdown. Furthermore, agar gel texture was more sensitive to adding oil, with changes observed in several textural properties of agar gels with no corresponding change in κ-carrageenan-locust bean gels. Adding oil did not change the oral processing pattern based on distance and velocity of jaw movement, along with temporal aspects of each chewing cycle. However, jaw velocity and movement were adjusted for differences in gel type. κ-carrageenan-locust bean gels generally required more muscle activity to prepare for swallowing, and increasing oil content decreased overall muscle activity for both gels. These results imply that gel structure, rather than the amount of oil filler, determined the oral processing pattern. Graphical abstract: Image 1 Highlights: The effect of added fat on gel cohesiveness and adhesiveness depended on gel type. Adding oil did not change the oral processing pattern. Stress intensity factor for fracture and muscle activity explained sensory hardness. Jaw movement correlated with mechanical and sensory difference between gel types.